Incidence of Pathogenic Halophilic Vibrios in Frozen Fish Products - S., Sanjeev; P.R.G., Varma; T.S., Gopalakrishna Iyer (Fishery Technology, 2025)
Three hundred and eighty two samples consisting of iced and frozen fish products were collected from 23 processing factories situated in Kerala and Tamil Nadu for studying the incidence of pathogenic halophilic Vibrios. Halophilic Vibrios were isolated from 193 samples (50.52%). 171 samples (44.76%) were found to be the carriers of pathogenic halophilic Vibrios. Nine species of pathogenic halophilic Vibrios and nine species of non-pathogenic halophilic Vibrios were isolated from these samples. Among pathogenic organisms, Vibrio cincinnatiensis was found to be the dominant species (18.06%) followed by Vibrio alginolyticus (15.18%), Vibrio parahaemolyticus (9.42%), Vibrio vulnificus (5.24%) etc. Vibrio harveyi was the major species among non-pathogenic halophilic Vibrios (12.30%).